Crime and punishment - Dostoyevsky, Fyodor, 1821-1881; Garnett, Constance, 1861-1946 (Mineola, N.Y. : Dover Publications, 2001)
A desperate and impoverished student named Raskolnikov commits a murder, thinking he is above moral law, but eventually must confront his inner mind and consequences. This is an intense psychological study, terrifying murder mystery, and fascinating detective thriller, instilled with philosophical, religious and social commentary
Originally published: London : Heinemann, 1914. With new introd
Keywords: Saint Petersburg (Russia) -- Fiction